The Religionization in Alevi Culture: An Exploratory Study on Spiritual Leaders (Dedes) - Işık, Nuran Erol (Annual review of the sociology of religion, 2021)
The multidimensionality of religious freedom and its rootedness in historical, socio-legal and socio-political contexts can be clearly exemplified through the phenomenon of Alevism in Turkey. Alevi culture has an age-old traditional structure, and thus a comprehensive critical approach is needed in the understanding of the ambivalences of ordinary religious belonging, and its transformation through formal structures, such as the European Courts of Human Rights (ECtHR). The effort to define modern Alevism in such a macro process requires a focus on the legal processes, and how these are understood, mediated and negotiated by a diverse group of mystical/spiritual leaders (dedes). The findings of this chapter emerge from in-depth interviews with eight dedes in Turkey.